In vitro Dissolution and in vivo Bioequivalence Evaluation of Two Brands of Isosorbide 5-mononitrate Sustained Release Tablets - Kim, Y.-H.; Choi, K.-S.; Kam, S.-H.; Lee, K.-H.; Park, J.-S. (Arzneimittelforschung, 2012)
The purpose of the present study was to test a sustained release-tablet newly formulated with synthetic paraffin and compare its bioequivalence to that of the Imdur® Long-Acting tablet, based on the guidelines of the Korean Food and Drug Administration.Dissolution test was performed in 4 different dissolution media. A LC/MS/MS method of isosorbide 5-mononitrate in human plasma was validated. In vivo bioequivalence tests of the 2 isosorbide 5-mononitrate tablets were performed in both preprandial and postprandial states.A comparative dissolution test gave similar results for both tablets in all dissolution media tested: 40% dissolution in pH 1.2 at 2 h and 80% dissolution in pH 4.0, pH 6.8, or water at 10 h. In a bioequivalence study to compare 2 tablets, the mean total area under the curve (AUCt) and peak concentration (Cmax) in the fasted state were 8 476.0 ng · h/mL and 540.4 ng/mL, respectively, for the Imdur® Long Acting Tablet 60 mg, and 8 701.4 ng · h/mL and 564.2 ng/mL, respectively, for the test tablet. The mean AUCt and Cmax in the fed state were 8 793.5 ng · h/mL and 559.9 ng/mL, respectively, for the Imdur® Long-Acting tablet 60 mg, and 8 639.8 ng · h/mL and 617.9 ng/mL, respectively, for the test tablet. The 90% confidence intervals using log transformed data were within the acceptable range of 0.8 − 1.25.Based on these statistical analyses, we conclude that the test tablet is bioequivalent to the Imdur® Long-Acting tablet 60 mg in both the preprandial and postprandial states.
Keywords: sustained release; isosorbide 5-mononitrate; in vitro dissolution; bioequivalence